2022
DOI: 10.3892/etm.2022.11700
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of cerium oxide on testicular function and oxidative stress after torsion/detorsion in adult male rats

Abstract: Testicular torsion (T)/detorsion (D) can cause testicular injury due to the rotation of the spermatic cord and its vessels, therefore it represents an urological emergency that is surgically treated. Oxidative damage occurs in the testis and distant organs because of the overproduction of free radicals and overexpression of proinflammatory cytokines by reperfusion after surgery. Cerium oxide (CeO 2 ) nanoparticles, a material also known as nanoceria, have regenerative antioxidant properties on oxidative stress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 88 publications
0
11
0
Order By: Relevance
“…Apoptosis happens when this apoptosome activates the initiator caspase-9 and the effector caspase-3 [32,33]. Furthermore, it has been demonstrated that lupeol downregulates caspase-3 in the experimental cerebral IR model through the PI3K/Akt signaling pathway [17,30].…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis happens when this apoptosome activates the initiator caspase-9 and the effector caspase-3 [32,33]. Furthermore, it has been demonstrated that lupeol downregulates caspase-3 in the experimental cerebral IR model through the PI3K/Akt signaling pathway [17,30].…”
Section: Discussionmentioning
confidence: 99%
“…Pre-adolescent patients sometime present late due to shyness regarding conveying their condition to parents. The protective effect of cerium oxide (CeO 2 ) on testicular function is being explored in experimental studies [ 21 ]. CeO 2 reduces oxidative stress, cell trauma, and death in testis tissue in experimental rats.…”
Section: Discussionmentioning
confidence: 99%
“…CeO 2 reduces oxidative stress, cell trauma, and death in testis tissue in experimental rats. In this study rats in the CeO2 group demonstrated significantly milder tissue lesions compared with those in the control group [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The animals were fed a standard pellet diet and allowed to drink water ad libitum. The dose of ketamine and Rompun administered to the rats was in accordance with the study by Yesil et al (15).…”
Section: Methodsmentioning
confidence: 96%